Trade realignment position in ECOWAS with gravity model. (10th May 2019) - Azu, Nnanna P.
This paper assesses the realignment position of trade in West African region with respect to the emergence of China and India vis-a-vis trade flow with traditional trade partners. Applying PPML technique with importer, exporter, and year fixed effect, the bilateral trade effects between ECOWAS and her trade partners are captured with dummy. These allow trades to be represented from both sides of its occurrences (import and export) rather than viewing from one side of it. Results revealed that ECOWAS trade with her emerging and traditional trade partner increased over time but rate of increases are reducing with the traditional partners - China and India are accumulating more market shares towards displacing these old friends. Given the trend, in no long time, there could be a fundamental realignment of trade from traditional trade partners for envisaged reliance on China and India.